Sarcoma botrioide. Reporte de un caso. - García Suárez, Manuel; Urbizo Cañón, Miguel; Montes de Oca Rodríguez, Eloy; Fong Aldama, Francisco; Luzardo Almeida, Epifania (Revista Cubana de Pediatría, 2023)
Se presenta un caso de sarcoma botrioide.